Total Hip and Knee Arthroplasty Implant Revision Risk to 5 Years From a State-wide Arthroplasty Registry in Michigan - Richard E. Hughes, PhD; Huiyong Zheng, PhD; Tae Kim, MHSA; Brian R. Hallstrom, MD (Arthroplasty Today, 2023)
Background: Information on the revision risk of implants is useful for improving the quality of care for elective hip and knee arthroplasty. The purpose of this study was to report on the revision risk of implants using a state-wide registry in the United States. Methods: The Michigan Arthroplasty Registry Collaborative Quality Initiative systematically collects data on elective primary and revision hip and knee arthroplasty cases in Michigan. It contained data on 139,970 hip and 245,499 knee arthroplasty cases from February 15, 2012, to December 31, 2021. Kaplan-Meier estimates of revision risk were computed using time to first revision as the dependent variable, and the results were computed and expressed as the cumulative percent revision (CPR). CPR estimates were computed for all implants having at least 500 cases in the Michigan Arthroplasty Registry Collaborative Quality Initiative dataset. Results: At 5-years postoperatively, elective primary conventional total hip arthroplasty implant stem/cup combinations had CPR values from 0.95% (0.39%-2.30%, 95% confidence intervals [CI]) to 5.77% (4.22%-7.85%, 95% CI), and elective primary total knee arthroplasty CPR ranged from 1.10% (0.64%-1.89%, 95% CI) to 12.52% (8.37%-18.50%, 95% CI). Unicondylar knee arthroplasty CPR at 5-years went from 4.23% (3.54%-5.06%, 95% CI) to 7.13% (6.20%-8.20%, 95% CI). Conclusions: The wide variation in CPR points to the need for surgeons to choose implants wisely to improve quality of care.